Social Media Approval Reduces Emotional Arousal for People High in Narcissism: Electrophysiological Evidence - Nash, Kyle; Johansson, Andre; Yogeeswaran, Kumar (Frontiers in Human Neuroscience, 2019)
We used event-related potentials (ERPs) to examine if posting a ‘selfie’ and receiving validation from others in the form of ‘likes’ on social media can help narcissists reduce psychological distress. After all participants completed the narcissistic personality inventory (NPI) and experienced social exclusion, participants completed an auditory startle task that elicits the P3 to white noise—an ERP component that reflects emotional arousal and is sensitive to psychological distress. Participants were then randomly assigned to either view a personal ‘selfie’ that quickly received a significant number of ostensibly real ‘likes’ (selfie with likes condition), view a ‘selfie’ with no feedback (selfie only condition), or view a neutral picture before (neutral picture condition) completing the auditory startle task again. Results revealed that participants high on the leadership/authority subscale of the NPI in the ‘selfie’ with ‘likes’ condition demonstrated a pre-post manipulation decrease in P3 mean amplitude, relative to participants in the other two conditions. These results suggest that approval via social media can help certain kinds of narcissists alleviate distress from social exclusion.